Curcumin Supplementation Improves Growth Performance and Anticoccidial Index by Improving the Antioxidant Capacity, Inhibiting Inflammatory Responses, and Maintaining Intestinal Barrier Function in IEimeria tenella/I-Infected Broilers - Chen, Yan; Liu, Liheng; Yu, Longfei; Li, Shuo; Zhu, Nianhua; You, Jinming (Animals (Basel), 2024)
Information about the effect of curcumin supplementation on the cecum of Eimeria tenella-infected broilers is scarce. This study examined the effects of curcumin on the growth performance, antioxidant system, intestinal integrity, and microbiota structure of broilers infected with E. tenella. Thus, this study provided a reference for using curcumin as a healthy feed additive. This study was conducted to investigate the effects of dietary curcumin supplementation on growth performance, anticoccidial index, antioxidant capacity, intestinal inflammation, and cecum microbiota in broilers infected with Eimeria tenella. A total of 234 one-day-old broilers were categorized into three treatments, with six replicates per treatment containing 13 broilers each. The three treatments included the control group, Eimeria tenella group, and Eimeria tenella + curcumin (200 mg/kg) group. The feeding trial lasted for 42 days, during which the broilers were orally administered with 0.9% saline or 5 × 10[sup.4]Eimeria tenella oocysts on day 14 of the study. On day 17 and day 21, one bird per replicate was selected for slaughtering. Results indicated an increased survival rate and anticoccidial index and improved productive performance in coccidia-infected broilers with curcumin supplementation. Furthermore, curcumin enhanced the serum antioxidant capacity in Eimeria tenella-infected broilers, evidenced by increased serum catalase activity (3d, 7d), as well as decreased malondialdehyde level (3d, 7d) and nitric oxide synthase activity (7d) (p < 0.05). Curcumin also improved intestinal inflammation and barrier function, evidenced by the downregulation of interleukin (IL)-1β (3d, 7d), TNF-alpha (TNF-α) (3d, 7d), and IL-2 (7d) and the up-regulated mRNA levels of claudin-1 (7d), zonula occludens (ZO-1; 3d, 7d), and occludin (3d, 7d) in the ceca of infected broilers (p < 0.05). Eimeria tenella infection significantly disrupted cecum microbial balance, but curcumin did not alleviate cecum microbial disorder in broilers infected with Eimeria tenella. Collectively, curcumin supplementation enhanced growth performance and anticoccidial index in Eimeria tenella-infected broilers via improving antioxidant ability and cecum inflammation without affecting cecum microbiota.